(untitled) (Minerva, 2019)
After a brief introduction describing the nature of the Mycenaean economy, an overview of the industrial production and trade in the Mycenaean society from the epigraphical sources is presented, by discussing the most outstanding studies published in this field. Six different industries are directly attested in the Linear B inscriptions: the perfume industry, the textile craftsmanship, the fur trade, the bronze working, the production of chariots, wheels and arms, and the furniture manufacture; there are also references to other eight craft activities in professional names. Mycenaean workers were mostly dependent personnel of the palaces. Finally, the textual references to Mycenaean trade are analysed, concluding with the problem of the ‘colectors’.